2022
DOI: 10.7150/ijbs.76134
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-related Proteins in Genome Stability: Autophagy-Dependent and Independent Actions

Abstract: It is emerging that autophagy-related proteins regulate the adaptive response to DNA damage in maintaining genome stability at multiple pathways. Here, we discuss recent insights into how autophagy-related proteins participate in DNA damage repair processes, influence chromosomal instability, and regulate the cell cycle through autophagy-dependent and independent actions. There is increasing awareness of the importance of these pathways mediated by autophagy-related proteins to DNA damage response (DDR), and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…However, the extent to which this is necessary in order to firmly prove causality should not be underestimated. The reason for this is firstly that, as opposed to what was assumed upon their initial identification in the 1990s, most, if not all, ATG proteins have non-autophagic cellular functions ( Yousefi et al, 2006 ; Gan and Guan, 2008 ; Baisamy et al, 2009 ; Hanson et al, 2010 ; DeSelm et al, 2011 ; Chung et al, 2012 ; Lee et al, 2012 ; Velikkakath et al, 2012 ; Maskey et al, 2013 ; Elgendy et al, 2014 ; Rohatgi et al, 2015 ; Chen et al, 2016 ; Joo et al, 2016 ; Joshi et al, 2016 ; Kaizuka and Mizushima, 2016 ; Nunes et al, 2016 ; Yang et al, 2016 ; Guo et al, 2017 ; Ramkumar et al, 2017 ; Wang and Kundu, 2017 ; Cadwell and Debnath, 2018 ; Saleiro et al, 2018 ; Galluzzi and Green, 2019 ; Hu et al, 2020 ; Lindner et al, 2020 ; Wu et al, 2020 ; Fang et al, 2021 ; Li et al, 2021 ; Mailler et al, 2021 ; Nieto-Torres et al, 2021 ; Sun et al, 2021 ; Zhang et al, 2022a ; Hamaoui and Subtil, 2022 ; Rajak et al, 2022 ; Chen et al, 2023 ; Deng et al, 2023 ; Liang et al, 2023 ; Wang et al, 2023 ; Tedesco et al, 2024 ; Tran et al, 2024 ; Yoon et al, 2024 ) that are likely to influence the cellular/phenotypic effects that are observed upon their knockdown, knockout or overexpression, and many of these functions affect pathways that are highly relevant to cancer. Therefore, in order to infer causality, the same cellular/phenotypic effect must be observed upon interference with a number of different ATGs.…”
Section: Discussion—limitations Of Current Studies Main Challenges An...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent to which this is necessary in order to firmly prove causality should not be underestimated. The reason for this is firstly that, as opposed to what was assumed upon their initial identification in the 1990s, most, if not all, ATG proteins have non-autophagic cellular functions ( Yousefi et al, 2006 ; Gan and Guan, 2008 ; Baisamy et al, 2009 ; Hanson et al, 2010 ; DeSelm et al, 2011 ; Chung et al, 2012 ; Lee et al, 2012 ; Velikkakath et al, 2012 ; Maskey et al, 2013 ; Elgendy et al, 2014 ; Rohatgi et al, 2015 ; Chen et al, 2016 ; Joo et al, 2016 ; Joshi et al, 2016 ; Kaizuka and Mizushima, 2016 ; Nunes et al, 2016 ; Yang et al, 2016 ; Guo et al, 2017 ; Ramkumar et al, 2017 ; Wang and Kundu, 2017 ; Cadwell and Debnath, 2018 ; Saleiro et al, 2018 ; Galluzzi and Green, 2019 ; Hu et al, 2020 ; Lindner et al, 2020 ; Wu et al, 2020 ; Fang et al, 2021 ; Li et al, 2021 ; Mailler et al, 2021 ; Nieto-Torres et al, 2021 ; Sun et al, 2021 ; Zhang et al, 2022a ; Hamaoui and Subtil, 2022 ; Rajak et al, 2022 ; Chen et al, 2023 ; Deng et al, 2023 ; Liang et al, 2023 ; Wang et al, 2023 ; Tedesco et al, 2024 ; Tran et al, 2024 ; Yoon et al, 2024 ) that are likely to influence the cellular/phenotypic effects that are observed upon their knockdown, knockout or overexpression, and many of these functions affect pathways that are highly relevant to cancer. Therefore, in order to infer causality, the same cellular/phenotypic effect must be observed upon interference with a number of different ATGs.…”
Section: Discussion—limitations Of Current Studies Main Challenges An...mentioning
confidence: 99%
“…As the names imply, the ATG proteins were identified through their roles in autophagy. Importantly, however, it has become increasingly evident that most, if not all, ATG proteins also have non-autophagic functions ( Velikkakath et al, 2012 ; Elgendy et al, 2014 ; Rohatgi et al, 2015 ; Kaizuka and Mizushima, 2016 ; Nunes et al, 2016 ; Yang et al, 2016 ; Cadwell and Debnath, 2018 ; Galluzzi and Green, 2019 ; Hu et al, 2020 ; Fang et al, 2021 ; Mailler et al, 2021 ; Zhang et al, 2022a ; Hamaoui and Subtil, 2022 ; Tedesco et al, 2024 ; Tran et al, 2024 ). This includes the by far most used autophagic marker LC3B ( Baisamy et al, 2009 ; Hanson et al, 2010 ; Chung et al, 2012 ; Ramkumar et al, 2017 ; Lindner et al, 2020 ; Nieto-Torres et al, 2021 ; Yoon et al, 2024 ), which originally was identified as a microtubule-associated protein in the 1980s ( Vallee and Davis, 1983 ) before its revelation as a mammalian homologue of yeast ATG8 in 2000 ( Kabeya et al, 2000 ).…”
Section: Autophagymentioning
confidence: 99%
“…Recent studies have shown that autophagy is directly involved in DNA damage response (DDR) 47 . p62 (SQSTM1) promotes the proteasomal degradation of FLNA and RAD51 components of the DNA repair machinery, and knockout of p62 increases the DNA repair rate 48 .…”
Section: Discussionmentioning
confidence: 99%
“…By intersecting DEGs and ARGs, 57 DE-ARGs were obtained. Gene co-expression analysis was performed on 57 DE-ARGs, and the results indicated a possible regulatory network of interaction between DE-ARGs 19,20 . GO and KEGG enrichment analysis of DE-ARGs revealed that DE-ARGs were mainly enriched in cellular autophagy and cellular response to stress 21,22 .…”
Section: Discussionmentioning
confidence: 99%